2015
DOI: 10.4238/2015.august.10.4
|View full text |Cite
|
Sign up to set email alerts
|

S-phase kinase-associated protein 2 expression interference inhibits breast cancer cell proliferation

Abstract: ABSTRACT. We investigated the expression of S-phase kinaseassociated protein 2 (SKP2) in breast cancer tissues, and the effects of SKP2-specific small interfering RNA (siRNA) interference on breast cancer cell proliferation. Thirty subjects provided breast cancer tissue samples and 18 subjects provided normal breast specimens for this study. The expression of SKP2 in breast cancer patient tissues and normal breast tissues was detected by western blotting analysis and reverse transcription-polymerase chain reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…Overexpression of Skp2 is associated with poor prognosis in breast cancer [23, 26]. Moreover, overexpression of Skp2 promoted cell proliferation in breast cancer cells [26], whereas inhibition of Skp2 suppressed cell proliferation in MDA-MB-231 cells [27]. In line with this, we observed the similar results, suggesting that Skp2 contributes to breast cancer cell growth.…”
Section: Discussionsupporting
confidence: 82%
“…Overexpression of Skp2 is associated with poor prognosis in breast cancer [23, 26]. Moreover, overexpression of Skp2 promoted cell proliferation in breast cancer cells [26], whereas inhibition of Skp2 suppressed cell proliferation in MDA-MB-231 cells [27]. In line with this, we observed the similar results, suggesting that Skp2 contributes to breast cancer cell growth.…”
Section: Discussionsupporting
confidence: 82%
“…Sun et al also reported that Skp2 expression is significantly higher in patients with invasive breast cancer than in normal breasts. 25 Our data also showed that high Skp2 expression positively correlated with reduced overall survival (OS), distant metastasis-free survival (DFS), relapse-free survival (RFS) and post-progression survival (PPS), suggesting a prognostic value of Skp2 in breast cancers. We also investigated the role of Skp2 and Skp2B in breast cancer cell growth, apoptosis and cell cycle arrest.…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, SKP2 silence significantly reduced breast cancer cell MDA-MB-231 proliferation. This study could be the experimental basis for further investigation and potential clinical application [113].…”
Section: Skp2 Inhibitorsmentioning
confidence: 87%